2023
DOI: 10.3390/ijms241512333
|View full text |Cite
|
Sign up to set email alerts
|

Protaetia Brevitarsis-Derived Protein Hydrolysate Reduces Obesity-Related Colitis Induced by High-Fat Diet in Mice through Anti-Inflammatory Pathways

Abstract: Ulcerative colitis is an inflammatory bowel disease characterized by inflammation in the mucosal and submucosal layers of the colon. Obesity is closely related to the occurrence and progression of colitis. The most plausible mechanism linking obesity and colitis is an excessive adipogenesis-related inflammatory response, which causes mucosal dysfunction. Obesity and colitis are linked by several etiologic mechanisms, including excessive adipogenesis, lipotoxicity, pro-inflammatory adipokines/cytokines, macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In addition, previous studies reported that LPS-induced inflammatory responses in RAW 264.7 macrophage and BV-2 microglia cells were improved by treatment with P. brevitarsis [ 23 , 44 ]. Treatment with P. brevitarsis -derived protein hydrolysate was also reported to result in the improvement of systemic inflammation through a decrease in the levels of cytokines, including IL-6, IL-17a, IL-1β, and TNF-α, in HFD-induced mice [ 45 ]. Treatment with a water extract of P. brevitarsis resulted in improved hippocampal neurodegeneration in rats with TMT-induced neuroinflammation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies reported that LPS-induced inflammatory responses in RAW 264.7 macrophage and BV-2 microglia cells were improved by treatment with P. brevitarsis [ 23 , 44 ]. Treatment with P. brevitarsis -derived protein hydrolysate was also reported to result in the improvement of systemic inflammation through a decrease in the levels of cytokines, including IL-6, IL-17a, IL-1β, and TNF-α, in HFD-induced mice [ 45 ]. Treatment with a water extract of P. brevitarsis resulted in improved hippocampal neurodegeneration in rats with TMT-induced neuroinflammation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%